Integrated Thinking, Reporting and Organisational Change: The Case of Integrated Reporting in South Africa - Gibson, Donald J.D. (2017)
The purpose of this research report is to document, understand and describe the extent to which integrated thinking and reporting has affected business practices in South African companies and resulted in intra-organisational change. It investigates how and why change is taking place and what the benefits of the change have been. The research adopts qualitative research methods incorporating a case study and involving semi-structured interviews with Johannesburg Stock Exchange listed companies rated as having high quality integrated reports and leading ESG performance, documentary analysis and participant observation. A total of nine interviews were held with representatives from finance, strategy, investor relations, sustainability and corporate affairs, in nine companies. A thematic analysis of the interview transcripts is undertaken using qualitative coding techniques, and case material is interpreted and theorised through Laughlin’s (1991) organisational change framework. The case narrative and theorisation show that integrated thinking and reporting did lead to intra-organisational change which had several impacts on company and societal value creation. It also showed that changes driven by integrated thinking and reporting have shifted firm ethos and therefore display the hallmarks of more fundamental ‘morphogenetic’ change. A limitation of this research project is the small number of company participants, the limited diversity of views obtained within companies, and the focus on South Africa only. The research does however empirically document the influences of integrated thinking and reporting on organisational change in the South African context, and the case analysis has identified several implications for practice and policy.